Queen's Park Hotel, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2010)
This postcard shows the front of the Queen's Park Hotel which is located opposite the Queen's Park Savannah. Taxis are parked outside the hotel.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Historic hotels--Trinidad and Tobago; Hotels--Trinidad and Tobago; [1940]; Cities and towns--Trinidad and Tobago--Port of Spain; Architecture--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Transportation--Trinidad and Tobago; Taxicab industry--Trinidad and Tobago; Taxicabs--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)